Overweight/Obesity and Associated Factors Among Second Cycle Primary School Children in Kirkos Sub-City, Addis Ababa, Ethiopia - Kidus Fitsum MPH; Gudina Egata PhD; Melake Demena MPH; Berhe Gebremichael MPH (SAGE Publishing, 2021)
Background Although overweight/obesity is becoming a public health issue in low income countries, there is a paucity of evidence concerning overweight/obesity in Ethiopia. The aim of the study was to assess the magnitude of overweight/obesity and associated factors among second cycle primary school children in Kirkos Sub-City, Addis Ababa, Ethiopia. Methods A school based cross-sectional study was conducted among 482 children from May to June, 2019. Data were collected using a questionnaire and checklist. Data were entered using EpiData version 3.1 and exported into SPSS version 22.0. Bivariable and multivariable logistic regression analyses were done to identify factors associated with overweight/obesity. Level of statistical significance was declared at p ≤ 0.05. Results The overall magnitude of overweight/obesity was 21.2%. The magnitude of overweight was 13.7% while obesity was 7.5%. Vehicle availability, being from private school, not having friend(s), preferring sweet foods, eating breakfast irregularly, watching movies/Television while eating and physical inactivity were the factors significantly associated with overweight/obesity among second cycle primary school children. Conclusions The magnitude of overweight/obesity was high in the study area. Therefore, health and education sectors should promote healthy lifestyle to curb child overweight/obesity.